Socialization of the Indian child - Sinha, Durganand (ed.) (New Delhi, 1981)
There are not many hardcore empirical studies on the processes governing socialisation of the Indian child and very little is available in print. This book brings together researches and papers of eminent psychologists from all over India presented during a seminar held at the U.G.C. Centre of Special Assistance on Psychological Study of Social Change and National Development, the Department of Psychology, Allahabad University. The topics cover socialisation in different ethnic and socio-cultural groups, socialisation and psychological differentiation, socialisation in the growth of political identity, prejudice and aggression, and a discussion on strategies of researches and methodology in the area. These eleven papers provide a glimpse of researches on socialization of the Indian child and are likely to be of immense interest to educationists, psychologists, social anthropologists and those actively engaged in child-care and development.
Keywords: Socialization